Dietary fiber antioxidant properties of mangifera pajang kort. peels and their synergistic health effects on hypercholesterolemic rats - Saleh Hassan, Fouad Abdulrahman (2012)
The fruit of Mangifera pajang Kort., known as bambangan is an underutilised fruit that is found in Malaysia (Sabah and Sarawak). Its size is about 3 times as large as commercial mango with a high amount of peel. The study was aimed to characterize the peels and investigate its effect on lowering cholesterol of hypercholesterolimic rat model. Bambangan peels are rich in dietary fiber and have been shown to contain high amount of valuable compounds such as polyphenols that should be strongly considered for exploitation. Dietary fiber (DF) and several properties of bambangan peels related to its nutritional quality were investigated. The physicochemical properties and antioxidant capacity of fiber rich peel powder (FRPP) obtained from bambangan peels were characterized. Chemical composition of soluble dietary fibre (SDF) and insoluble dietary fibre (IDF) for their related polysaccharides using RI-HPLC were also determined. The FRPP had a high amount of DF (72.3 g/100 g dry weight) with a balanced SDF/IDF ratio (1:1.2). The FRPP had a high glucose retardation index, water-holding capacity (WHC), oil-holding capacity (OHC), and swelling property. As FRPP was characterized for its content of DF, it also analyzed for its content of phenolic compounds in an acidified methanolic extract obtained from fully ripe bambangan (M. pajang Kort.) peel. The antioxidant capacity of the FRPP as determined by Ferric Reducing Antioxidant Power (FRAP) and 1, 1-diphenyl-2- picrylhydrazyl (DPPH) assays exhibited strong potency with a high value (44 mg/mL) of IC50, due to the presence of associated polyphenols (98.3 mg GAE/g FRPP) as determined by Folin–Ciocalteu method. Sixteen phenolic compounds, were identified and quantified in FRPP using a HPLC-DAD coupled to Quantum-electrospray ionization /mass spectrometry (TSQ Quantum Ultra-ESI-MS) to confirm peaks identification, by comparing their retention times, UV–Vis absorption spectra and mass spectra with authentic standards. Gallic acid, p-coumaric acid, ellagic acid, protocatechuic acid and mangiferin were the major compounds among the identified 16 phenolics in M. pajang Kort. peels with amount of 20.9, 12.7, 7.3, 5.4 and 4.8 mg/g FRPP, respectively. Investigation of the potential hypolipidemic effect of FRPP was performed using an animal model of dietary-induced hypercholesterolemia rats. For 6 weeks rats were fed cholesterol-free diets as a negative control, diets supplemented with 2% cholesterol to induce hypercholesterolemia (positive control), fiber control diet containing 5% cellulose as standard DF and test diets supplemented with 70 g of FRPP per kilogram (providing 5% DF) and 97 g/ kg (providing 7% of DF). Beside the nutritional parameters, lipid profile, malondialdehyde (MDA), toxicity parameters, total antioxidant status (TAS), the activity of the antioxidant enzymes glutathione peroxidase (GPX) and superoxide dismutase (SOD) were measured in plasma. In addition, the fecal bile acids excretions were also determined utilizing HPLC-DAD. The consumption of FRPP in hypercholesterolemic condition improved the animals’ blood lipid profile, liver and kidney functions and reduced lipid peroxidation marker with increasing the excretion of bile acid. Thus, suggested that the potential contribution of FRPP in a cardiovascular risk reduction. Hypercholesterolemia and hypertriglyceridemia were recognized as a result of the cholesterol-rich diets. FRPP exhibited an important hypolipidemic action, returning triglyceride (TG) levels in hypercholesterolemic animals to normal values. The hypocholesterolemic effect of FRPP with dose of 7% was observed, reducing total and low-density lipoprotein cholesterol (-63%, -76%, respectively). Decreased lipid peroxidation in plasma as a consequence of FRPP intake was found in hypercholesterolemic treated groups. Increased the fecal bile acids excretion as a result of FRPP intake was observed in all treated groups. This could be attributed to the high DF content. All these favorable findings might be related to its DF content and the natural presence of antioxidant polyphenols that prevent lipid peroxidation. Findings of the present study had indicated that the incorporation of FRPP into hypercholesterolemic diet improved the lipid profile and reduced lipid peroxidation. It might defend against cellular damage and contribute to a reduction of cardiovascular risk. The findings in the current study might be related to the synergistic effect of SDF (33% d.w) and polyphenols in FRPP. FRPP properties showed that peels of Mangifera pajang Kort. are rich source of DF and other bioactive compounds that could be used as functional food ingredients. It also exhibited an important health effect as lowering cholesterol thus would put forward the potential application of bambangan peels to be incorporated into food formulation.